2018
DOI: 10.1155/2018/4028297
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine: An Antioxidant Remedy for the Survival of Cardiomyocytes under Hyperglycemic Condition

Abstract: Background Metabolic alterations as hyperglycemia and inflammation induce myocardial molecular events enhancing oxidative stress and mitochondrial dysfunction. Those alterations are responsible for a progressive loss of cardiomyocytes, cardiac stem cells, and consequent cardiovascular complications. Currently, there are no effective pharmacological measures to protect the heart from these metabolic modifications, and the development of new therapeutic approaches, focused on improvement of the oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 78 publications
7
12
0
1
Order By: Relevance
“…Romestaing et al [32] have demonstrated the increase in COX expression mediated by MCDD that alters mitochondrial metabolism, as demonstrated with elevated ROS level. In addition, other studies have described the capacity of LC to attenuate ROS accumulation and cardiac dysfunctions in ischemic or irradiated hearts [44,45] and to decrease oxidative stress in normal and hyperglycemic cardiomyocytes [46,21]. The present study confirmed that LC attenuates ROS production in the liver (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Romestaing et al [32] have demonstrated the increase in COX expression mediated by MCDD that alters mitochondrial metabolism, as demonstrated with elevated ROS level. In addition, other studies have described the capacity of LC to attenuate ROS accumulation and cardiac dysfunctions in ischemic or irradiated hearts [44,45] and to decrease oxidative stress in normal and hyperglycemic cardiomyocytes [46,21]. The present study confirmed that LC attenuates ROS production in the liver (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have suggested the role of oxidative pathways as favourable targets for the treatment of NAFLD [19]. LC has been recognized as a nutritional supplement with anti-oxidative properties [20] and used as an adjunctive therapy in various heart conditions with promising results [21]. In particular, Strilakou et al have described the beneficial effects of LC on a cardiomyopathy rat model fed with a choline-deficient diet [22].…”
Section: Introductionmentioning
confidence: 99%
“…1a. These doses were chosen based on literature data [18,19]. We studied HepG2 growth capacity to evaluate the absence of cytotoxic effects.…”
Section: Cell Line Culture Conditionsmentioning
confidence: 99%
“…Our group has recently demonstrated that LC could regulate cellular anti-oxidative responses [18][19][20]26]. Since mitochondria are the primary intracellular regulator of ROS balance, LC effect on mitochondrial activity in HepG2 cells was studied.…”
Section: L-carnitine Effects On Mitochondrial Biogenesis and Anti-oximentioning
confidence: 99%
See 1 more Smart Citation